2022
DOI: 10.1007/s12609-022-00469-9
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Time to Treatment for Breast Cancer: Existing Knowledge and Future Directions in the COVID-19 Era

Abstract: Purpose of Review Despite significant advances in detection and treatment for breast cancer, the breast cancer mortality rate for Black women remains 40% higher than that for White women. Timely work-up and treatment improve outcomes, yet no gold standard exists for which to guide providers. Recent Findings A large body of literature demonstrates disparities in time to treatment for breast cancer, and most studies show that Black women receive treatment later than their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Their study also assessed the influence of the location, type of institution (academic vs. community), and travel distance to the treatment facility and found that the lowest rate of BCT use happened in community cancer centers and among patients who traveled distances to their facility greater than 27.8 km, the latter suggesting that access to standard radiotherapy in urban vs. rural areas is variable and directly influences the use of BCT. A multitude of studies have demonstrated delays in time to treatment, including time to surgery by race [148,149]. In fact, a National Cancer Database Study by Jackson et al showed that 30.6% of non-Hispanic Black women had surgery more than 60 days after diagnosis compared to only 18% of White women [150].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Their study also assessed the influence of the location, type of institution (academic vs. community), and travel distance to the treatment facility and found that the lowest rate of BCT use happened in community cancer centers and among patients who traveled distances to their facility greater than 27.8 km, the latter suggesting that access to standard radiotherapy in urban vs. rural areas is variable and directly influences the use of BCT. A multitude of studies have demonstrated delays in time to treatment, including time to surgery by race [148,149]. In fact, a National Cancer Database Study by Jackson et al showed that 30.6% of non-Hispanic Black women had surgery more than 60 days after diagnosis compared to only 18% of White women [150].…”
Section: Surgical Treatmentmentioning
confidence: 99%